A STUDY OF ENGLISH SPEAKING PRESENTATION TECHNIQUES OF BACHELOR OF ARTS S TUDENTS IN ENGLISH PROGRAM AT MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY - Rajinda, khurleng (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2019)
The purposes of this study are 1) to study the English Speaking Presentation Techniques of Bachelor of Arts Students in English Program at Mahachulalong kornrajavidyalaya University. 2) to propose the solution of English Speaking Presentation techniques of Bachelor of Arts Students in English Program at Mahachularlong kornrajavidyalaya University. The number of the participnat are consited of 134 persons. The instrument used in this research is both qualitative and quantitative method. The tools used for collecting data were questionnaire, in-depth interview, and participant observation with students and then the information was analysed by using percentage, means, averages and standard deviation (S.D). The result of this study had found that the presentation techniques of the students were at high level of average and every question is not less than 3.50. The suggestion for presentation techniques had found that the students should prepare the topic, gathering information, more practice, gain more confidence. Furthermore, students should have enough information, and enough preparation.